(untitled) (Agricultural Engineering, 2016)
Agricultural nozzles usually produce a different drops size depending on the pressure and the physical condition (work life) of the nozzle besides producing a wide range of the drops spectrum in the spray cloud. In this paper the standard flat fan nozzles were investigated regarding the effect of the working pressure and the nozzle physical condition (new and worn nozzles). The size of drops and the spectrum of drops across the long axis of the spray pattern were examined by using Sympatec GmbH Laser Diffraction. Reducing the working pressure from 3 to 2 and then to 1 caused production of larger drops, also using worn nozzles (especially with lower pressure) changed the drops size which is expected to be produced from the new nozzles. The standard flat fan nozzles produced a wide range of the drops spectrum inside the spray cloud, generally small drops (less than 150 µm) concentrated in the middle of the spray pattern while the big drops (250-350µm) were situated on the edge positions (70 cm from the centerline) of the spray pattern.